Strengthening SFBT approach with self counseling to improve the ethics of politenees children - Muhammad Misbahul Huda (Ikatan Bimbingan dan Konseling Sekolah)
Humans are creatures with dynamic and ethical thinking styles. In today's reality there are still many ethical violations, especially courtesy in acting done by the child. environmental conditions, internal factors and technological sophistication are often the cause of ethical violation behavior. An educational counselor in this case has the responsibility to find effective and efficient solutions in dealing with ethical violations committed by his students. Implementation of counseling with collaboration The approach of Solution Focus Brief Tretment (SFBT) and self counseling is considered capable of raising awareness of the ethical enhancement of students' ethics because in the counseling process it involves expert counselors and personal roles.